Solar-Wind Hybrid Generation System Using Single Axis Solar Tracker - Farooq, Nasir; Farooq Khan, Yusera (Asian Journal of Electrical Sciences, 2018)
As the name suggests the aim of our paper is to enhance the generation of electricity of solar-wind hybrid generation system by using single axis solar tracker. Since the efficiency of solar energy system is less than 50%, so to increase solar energy conversion we are using single axis solar tracking system with solar panel. Since we are alternating non-conventional energy resources for conventional energy resources due to environmental reasons. Thus we have to take steps to enhance the energy conversion capacity of non-conventional energy resources so as to produce bulk electricity with less economy. That is why we are using single axis solar trackers with solar panel to increase the amount of electricity generation from solar-wind hybrid generation system to provide uninterrupted power supply for the load demand.